Problematic gaming in Malaysian university students: translation and psychometric evaluation of the Malay language versions of gaming disorder test and gaming disorder scale for young adults - Ghazi, Farah Raihana; Gan, Wan Ying; Tung, Serene En Hui; Chen, I Hua; Poon, Wai Chuen; Siaw, Yan Li; Ruckwongpatr, Kamolthip; Chen, Jung Sheng; Huang, Shih Wei; Griffiths, Mark D.; Lin, Chung Ying (SAGE Publications, 2023)
As research on gaming disorder (GD) is growing globally, the need for a valid and reliable instrument to assess GD has become crucial. Therefore, the present cross-sectional study translated and evaluated the psychometric properties of Gaming Disorder Test (GDT) and Gaming Disorder Scale for Young Adults (GADIS-YA) into Malay language versions. The sample comprised 624 university students (females = 75.6%; mean age = 22.27 years) recruited via an online survey from May to August 2022, using a convenience sampling method. Participants completed both GDT and GADIS-YA scales and other relevant measures including Bergen Social Media Addiction Scale (BSMAS), Internet Gaming Disorder Scale-Short Form (IGDS9-SF), and time spent on social media and gaming. Results showed that both instruments reported satisfactory internal consistency, and confirmatory factor analysis supported the one-factor structure for GDT and two-factor structure for GADIS-YA. Both scales were strongly correlated with each other and with the IGDS9-SF, BSMAS, and time spent on social media and gaming, supporting concurrent validity. Measurement invariance of both scales was confirmed across gender and gaming time. These findings suggest that the Malay versions of GDT and GADIS-YA are reliable and valid measures of problematic gaming among Malaysian university students.